OPTIMAL ENERGY MIX FOR ASMALL-SCALE DISTRICT HEATING SYSTEM IN R. N. MACEDONIA - Lazova, Elena; SHesho, Igor (University of Niš, Faculty of Mechanical Engineering, 2023)
The European Union aims to be an economy with zero greenhouse gas emissions by 2050. The integration of renewable energy sources (RES) into district heating systems (DHSs) is an ongoing process. With the localization of CO2 emissions, DHS allow easy control of the environmental impact. The integration of heating systems into a common source, i.e. connection to DHSs, enables the diversification of heat sources, which contributes to increased independency and reliability of the system's functioning, as well as optimizing the production price of heat. The purpose of this paper is to develop and simulate small district heating system with a heat demand of 7490MWh and a peak of 3470kW for the City of Ohrid, with optimal RES share in order to minimize production costs for heat. Several scenarios-systems are modeled and analyzed: solar thermal system, natural gas-fueled combined heat and power plant, photovoltaic plant, heat pumps and seasonal heat storage tank. Optimization of the considered system aims to be competitive to the existing individual heating systems.
Keywords: district heating, renewable energy sources